THE DIFFERENCES BETWEEN MONOLINGUAL AND BILINGUAL TEENAGER AND YOUNG ADULT LEARNERS IN LEARNING FOREIGN LANGUAGES - Boymurodova Feruza Ziyot kizi; Bahodirova Mohinur Muhiddin qizi (Western European Studies, 2025)
The purpose of this article is to analyse the contrast between Language learning strategies (LLS ) and proficiency of monolingual and bilingual learners among young adults and teenagers . This research was conducted with 210 who were 12 and 28 years old students in higher education and other type of learning centres. The methods of this research survey and an interview. Result from this study showed that bilingual students have many benefits in terms of cognitive flexibility, learning strategies such as transferring skills and learning environment and social interactions
Keywords: Language learning strategies; cognitive flexibility; transferring skills